How Writers Use Ghosts to Explore Grief in Contemporary Young Adult Fiction - Charlotte Taylor (Leaf Journal)
In this paper, I interrogate how contemporary YA writers use ghosts in their novels to explore ideas about adolescence and grief. Ghost stories are a well-known genre that thrill and entertain and in turn, the key purpose of YA Fiction is to provide teenage readers with books that help them make sense of the world. I explore why teenagers might enjoy ghost narratives, to look at the juxtaposition between the youthful reader, full of vitality enjoying stories that deal with death and the afterlife. I look at three contemporary titles that explore ideas about what it means to haunt and be haunted: The Astonishing Colour of After by Emily X R Pan (2018) in which a grieving teen is haunted by the spirit of her mother, who manifests as a red bird; A Skinful of Shadows by Frances Hardinge (2017), in which the central protagonist Makepeace is haunted by several spirits including a desolate dancing bear, and AfterLove by Tanya Byrne (2021) where Ash dies suddenly and learns what it is to be the ghost. I look at how these writers craft the ghosts in these stories, explore ideas about grief, and create spectral landscapes.